Introduction to Sufism: A Research Review in The Light of the Views of Muslim Thinkers - Mr.Muhammad Yaseen; Dr. Muhammad Imran Anwar (Journal of Religion and Society, 2025)
This study explores the curriculum of Sufism in Pakistan's religious seminaries (madaris), focusing on its challenges, impacts, and potential measures for improvement. Sufism, a mystical dimension of Islam, emphasizes inner purification and spiritual connection with the Divine. Despite its deep roots in Islamic tradition, Sufism's incorporation into the formal curricula of Pakistani madaris has faced several challenges.The research investigates these challenges, which include doctrinal disagreements, administrative hurdles, and societal perceptions. One significant challenge is the doctrinal tension between Sufi practices and more orthodox Islamic interpretations, often leading to a polarized environment within the educational institutions. Administratively, madaris often lack standardized curricula and trained faculty, which hampers the effective teaching of Sufi subjects. Additionally, the broader societal view, influenced by political and sectarian dynamics, affects the acceptance and implementation of Sufism in the educational framework.The study also examines the impacts of incorporating Sufism into the madrasa curriculum. Positively, it can promote values of tolerance, peace, and spiritual enrichment among students. Sufi teachings often emphasize compassion, humility, and love for all humanity, which can counteract radical tendencies and foster a more harmonious society. However, the improper integration of Sufi subjects, without a balanced and contextual approach, might lead to misinterpretations and misuse of Sufi practices.To address these issues, the study suggests several measures. First, there is a need for a well-defined and standardized Sufi curriculum that aligns with both traditional Islamic teachings and contemporary educational standards. Training programs for teachers specializing in Sufism are essential to ensure accurate and effective transmission of knowledge. Furthermore, fostering an environment of inter-sectarian dialogue within madaris can help mitigate doctrinal tensions and promote mutual respect and understanding In conclusion, the integration of Sufism into the curriculum of Pakistan's religious seminaries holds significant potential for spiritual and societal benefits. However, addressing the doctrinal, administrative, and societal challenges is crucial for its successful implementation. This study provides a comprehensive overview of these aspects and proposes actionable steps to enhance the teaching and understanding of Sufism in Pakistani madaris. The research contributes to the broader discourse on religious education reform and the role of Sufism in contemporary Islamic scholarship. Keyword: Sufism, Introduction, Concept, Aspects, Different Opinions, Necessity of Sufism, Importance of Sufism